Women's Income and Professional Participation in Indonesia: Gender Gap Analysis Based on GDI and GEI - Revilia, Regiana; Afriani, Dwi (SERUNAI, 2025)
This study analyzed the impact of the Gender Development Index (GDI) and the Gender Empowerment Index (GEI) on women's income and their engagement in the workforce across 38 provinces in Indonesia. The gender gap in economic access continues to be a persistent issue, notwithstanding recent enhancements evident in national gender development indices. While prior studies examined gender inequality in broader contexts, there has been a paucity of empirical research directly evaluating the impact of GDI and GEI on women's economic outcomes at the provincial level. This disparity underscored the necessity for a more targeted and data-centric examination. This study's uniqueness resides in its identification of an empowerment paradox, wherein elevated empowerment ratings did not invariably result in enhanced economic conditions for women. This research was driven by the necessity to furnish empirical information that may underpin gender-responsive economic policymaking and rectify discrepancies between formal gender accomplishments and actual economic involvement. A mixed methods approach utilizing a sequential explanatory design was implemented, commencing with quantitative analysis through Spearman’s correlation and linear regression, succeeded by qualitative interpretation to contextualize the statistical results. The results indicated that GDI had a positive and important effect on women's income and their participation in the workforce. Conversely, GEI had little impact on either metric, indicating that formal empowerment accomplishments lag behind meaningful economic advancement for women. The results demonstrated the need for measures that foster fundamental gender development and address structural barriers in the job market.